2022
DOI: 10.3390/ijms23105725
|View full text |Cite
|
Sign up to set email alerts
|

Bone Health in Children with Rheumatic Disorders: Focus on Molecular Mechanisms, Diagnosis, and Management

Abstract: Bone is an extremely dynamic and adaptive tissue, whose metabolism and homeostasis is influenced by many different hormonal, mechanical, nutritional, immunological and pharmacological stimuli. Genetic factors significantly affect bone health, through their influence on bone cells function, cartilage quality, calcium and vitamin D homeostasis, sex hormone metabolism and pubertal timing. In addition, optimal nutrition and physical activity contribute to bone mass acquisition in the growing age. All these factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 169 publications
(180 reference statements)
0
8
0
Order By: Relevance
“…Inflammation plays a crucial role in the progression, pathogenesis, and prognosis of vertebral fractures. [ 20 , 21 ] In this large-scale study, the SII was identified as an independent risk factor for all-cause mortality among patients with vertebral fractures. The results showed a significant association between high SII levels and increased all-cause mortality in these patients, even after adjusting for multiple variables.…”
Section: Discussionmentioning
confidence: 95%
“…Inflammation plays a crucial role in the progression, pathogenesis, and prognosis of vertebral fractures. [ 20 , 21 ] In this large-scale study, the SII was identified as an independent risk factor for all-cause mortality among patients with vertebral fractures. The results showed a significant association between high SII levels and increased all-cause mortality in these patients, even after adjusting for multiple variables.…”
Section: Discussionmentioning
confidence: 95%
“…All JIA patients in our study fulfilled the indications for performing DXA as the patients with JIA had at least 1 risk of developing low bone mass including chronic inflammation, joint destruction, and glucocorticoids treatment. 16,37…”
Section: Methodsmentioning
confidence: 99%
“…All JIA patients in our study fulfilled the indications for performing DXA as the patients with JIA had at least 1 risk of developing low bone mass including chronic inflammation, joint destruction, and glucocorticoids treatment. 16,37 The BMD results were analyzed by using the Prodigy Encore Software (version 7.53, standard scan mode). Measurements included BMD of the lumbar spines (L2-L4) (BMDLS) and BMD of the total body (BMDTB).…”
Section: Bone Mineral Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ho wever, it should be noted that the prevalence of JIA has not changed significantly over the past 5 years [1,2]. It has been demonstrated that the development of systemic autoimmune and inflammatory diseases, including JIA, is accompanied by a decrease in bone mineral density and an increased risk of bone fractures during childhood [3,4]. A decrease in bone mineral density is observed in all parts of the skeleton in children and adolescents with JIA, and up to 50 % of adults with a history of JIA [5].…”
Section: Introductionmentioning
confidence: 99%